The Influence Of Networking Abilities On Students' Digital Transformation Abilities - Bahasoan, Nizmah Ahmad; Saleh, Lukman (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The rapid development of digital technology has driven significant digital transformation across various sectors, including higher education. Digital transformation is not confined solely to technology adoption—it fundamentally involves alterations in how students think, collaborate, innovate, and develop competencies essential for their academic and professional growth. In this evolving landscape, students are expected to acquire digital transformation skills, which encompass adaptability in leveraging digital technologies to enhance academic performance, creativity, and readiness for the workforce. A critical factor that influences students’ digital transformation skills is their networking abilities. Networking skills refer to an individual's capacity to build, manage, and utilize social and professional networks effectively to access information and resources. Unfortunately, many students utilize technology predominantly for communication and entertainment, rather than for fostering their competency development. This gap highlights the untapped potential of student networks, which remain underutilized in academic contexts. This study aims to analyze the impact of networking skills on students’ digital transformation skills. The study employed empirical data collection methods, with initial analyses presenting statistically significant results that affirm the relationship between students' network capability and their digital transformation skills. For instance, the test results showed a t-value of 3.98 with 38 degrees of freedom and a significance value of 0.000 (p < 0.05), indicating a substantial difference between experimental and control groups. Consequently, the null hypothesis (H₀) was rejected, while the alternative hypothesis (H₁) was accepted, underscoring that enhanced network capability contributes positively to students' digital transformation capabilitiesUltimately, this study hopes to contribute theoretically to the understanding of digital transformation at the individual level and provide practical recommendations for universities to devise effective student learning and development strategies.